Perioperative Problems in Infants Having Pulmonary Hypertension Following Ketamine General Anesthesia - Fizzah Ali, Raja Altaf Ahmed Khan, Adeel Bashir, Syed Saqib Khalid, Zeeshan Aslam, Muhammad Zafar Rana, (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: In adolescents, pulmonary arterial hypertension (PAH) is linked through the substantial postoperative danger of serious problems such as pulmonary severe illness and heart attack. The efficacy of ketamine anesthesia inside this patient group is still unknown. Examine the health information about children having PAH in the past to identify the kind and occurrence of peri-procedural issues, as well as whether ketamine medication been connected to peri-procedural difficulties. Methods: Adolescents having PAH who had general anesthesia for operations throughout the one-year interval (May 2020–April 2021) were eligible to participate. Specifics concerning the patient, PAH, surgery, anesthesia, and post-procedural course were recorded, as well as any untoward events that occurred while or inside 48 hours of the operation. Complication rates were reported separately for each surgery. The relationship among ketamine and peri-procedural problems has been investigated. Results: Seventy-five children (median age 8.4 years, average weight 23 kg) had 193 surgeries performed on them. PAH intensity has been classified as mild (26%), medium (37%), or severe (37%). (41 percent). Medical intervention (n = 21), moderate surgery (n = 28), cardiac catheterization (n = 129), and nonsurgical treatments (n = 18) have been performed. During 152 surgeries, ketamine has been given. Thirty mild problems and nine significant problems reported identified. Cardiac arrest occurred in 0.79 percent of cardiac catheterization operations, 11 percent of significant medical procedures, and 2.7 percent of all processes. There has been no death as a result of the surgery. Ketamine administration was not linked to increases in problems. Conclusion: Ketamine looks to be a safe anesthetic alternative for patients. people suffering from PAH We present data on cardiopulmonary resuscitation rates and significant death rates that are higher than that found. Keywords: Pulmonary Arterial Hypertension, Infants, Hypertension, Cardiac Arrest.